Relationship between Emotions and the Job Performance of Private Sector Workers Working Online in Selangor - Mohamed Shaharudin, Syahirah Izni; Muhammad Ammar Shafi (Research in Management of Technology and Business, 2022)
The objectives of this research are to identify the level of the job performance of private sector workers working online, to determine the emotion level of private sector workers working online and to study the relationship between emotions and the job performance of private sector workers working online. There for all intents and purposes is a kind of non-normal distribution based on the results of the normality test, and the Spearman correlation analysis particularly is used in the study, which definitely shows that the three kinds of main categories really are respondents’ demographic information, job performance, and sort of private sector workers’ emotions, or so they actually thought. results of the normality test, and the Spearman correlation analysis essentially is used in the study, which specifically shows that the three definitely main categories really are respondents’ demographic information, job performance, and sort of private sector workers’ emotions, which essentially is quite significant. The study’s overall kind of goal really is to assess the relationship between job performance and emotion among of private sector workers working online in Selangor, which basically is quite significant. The three sorts of main categories are respondent’s demographic information, job performance, and sort of private sector workers emotions in a basically major way. The data for all intents and purposes has been analysed in this chapter, and the three particularly main categories in the questionnaire essentially have been discussed in a subtle way.